Challenges to the management of human resources for health 2005 - 2015 - Novick, Marta (PAHO Washington, D.C.US, 2006)
Analyses the most salient issues affecting public health labour management. Describes the changing relationships among the diverse actors in the field of human resources, as well as the technical cooperation needs that have emerged from the current scenario.